MAJAS DAN RETORIK DALAM IKLAN KAMPANYE CALON GUBERNUR DAN CALON WAKIL GUBERNUR DKI JAKARTA TAHUN 2012 - Endang Wahyuningsi; Ermanto .; Hasanuddin . (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: The purpose of this researched was to (1) describe the benefit of figure speech in campaign advertising of Governor and Vice Governor Candidat in DKI Jakarta 2012 at Kompas, Republika, and Suara Pembaruan, (2) describe the benefit of rhetoric in campaign advertising of Governor and Vice Governor Candidate in DKI Jakarta 2012 at Kompas, Republika, and Suara Pembaruan. This research is qualitative research that had content analysis. The data research was a sentence or speech in campaign advertising of Governor and Vice Governor Candidate in DKI Jakarta 2012 at Kompas, Republika, and Suara Pembaruan. The results of this research showed two things. First, the utilization figure of speech in campaign advertising of Governor and Vice Governor Candidate in DKI Jakarta 2012 at Kompas, Republika, and Suara Pembaruan gave the poetic elements and had metaphor meaning or had additional meaning. Second, utilization of rhetoric in campaign advertising Governor and Vice Governor Candidates in DKI Jakarta 2012 at Kompas, Republika, and Suara Pembaruan for delivering the meanings, explanation, pressing and ornaments directly, and also have impressed by reader. Kata kunci: majas; retorik; iklan kampanye, calon gubernur, calon wakil gubernur